2023
DOI: 10.1177/20552076231171969
|View full text |Cite
|
Sign up to set email alerts
|

The role of mobile health in prevention, diagnosis, treatment and self-care of COVID-19 from the healthcare professionals’ perspectives

Abstract: Background To facilitate disease management, understanding the attitude of healthcare professionals regarding the use of this tool can help mobile health (mHealth) program developers develop appropriate interventions. Aims To assess the perspective of healthcare professionals regarding the contribution of mobile-based interventions in the prevention, diagnosis, self-care, and treatment (PDST) of COVID-19. Methods This is a survey study conducted in 2020 in Iran with 81 questions. In this study mHealth function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…This suggests that mHealth could be a potential alternative to the standard laboratory-based confirmatory diagnosis to find COVID-19 cases. Previous studies have shown that mHealth technologies could have significant contributions to self-care for patients with COVID-19 [35] and the dissemination of COVID-19-related information [36,37]. As mHealth and other digital health technologies are yet at an early stage of development in Africa, the capacity and readiness of each country to effectively adopt, implement, and scale up digital health interventions require due diligence [38][39][40][41][42].…”
Section: Principal Findingsmentioning
confidence: 99%
“…This suggests that mHealth could be a potential alternative to the standard laboratory-based confirmatory diagnosis to find COVID-19 cases. Previous studies have shown that mHealth technologies could have significant contributions to self-care for patients with COVID-19 [35] and the dissemination of COVID-19-related information [36,37]. As mHealth and other digital health technologies are yet at an early stage of development in Africa, the capacity and readiness of each country to effectively adopt, implement, and scale up digital health interventions require due diligence [38][39][40][41][42].…”
Section: Principal Findingsmentioning
confidence: 99%